Large‐Pore Mesoporous‐Silica‐Coated Upconversion Nanoparticles as Multifunctional Immunoadjuvants with Ultrahigh Photosensitizer and Antigen Loading Efficiency for Improved Cancer Photodynamic Immunotherapy. Issue 52 (2nd November 2018) - Ding, Binbin; Shao, Shuai; Yu, Chang; Teng, Bo; Wang, Meifang; Cheng, Ziyong; Wong, Ka‐Leung; Ma, Ping'an; Lin, Jun
Abstract: Reported immunoadjuvants still have many limitations, such as inferior cellular uptake capacity and biocompatibility, overly large particle sizes, single function, and unsatisfactory therapeutic efficacy. Here, large‐pore mesoporous‐silica‐coated upconversion nanoparticles (UCMSs) with a size of less than 100 nm are successfully prepared by a typical silica sol–gel reaction using mesitylene as a pore‐swelling agent and are applied as a novel immunoadjuvant. The obtained UCMSs not only show significantly higher loadings for the photosensitizers merocyanine 540 (MC540), model proteins (chicken ovalbumin (OVA)), and tumor antigens (tumor cell fragment (TF)), but also are successfully employed for highly efficient in vivo vaccine delivery. The prepared UCMSs–MC540–OVA under 980 nm near‐infrared irradiation shows the best synergistic immunopotentiation action, verified by the strongest Th1 and Th2 immune responses and the highest frequency of CD4 +, CD8 +, and effector‐memory T cells. Additionally, nanovaccines UCMSs–MC540–TF can more effectively inhibit tumor growth and increase the survival of colon cancer (CT26)‐tumor‐bearing BALB/c mice compared with either photodynamic therapy or immunological therapy alone, suggesting the enhanced immunotherapy efficacy and clinical potential of UCMSs as immunoadjuvants for cancer immunotherapy. Abstract : Monodispersed large‐pore mesoporous‐silica‐coated β‐NaYF4 :20%Yb, 2%Er upconversion nanoparticles (UCMSs) as multifunctional immunoadjuvants are prepared by a typical silica sol–gel reaction using mesitylene as a pore‐swelling agent. By mixing with merocyanine 540 (MC540) and tumor cell fragment (TF), the obtained nanovaccine UCMSs–MC540–TF exhibits excellent effects of photodynamic immunotherapy.